George Sale's Pioneering Translation: Unveiling 'The Koran' – A Critical Exploration of Early English Interpretations" - Hüseyin Çaksen; Khalid Hussain Mir (al-Afkar, Journal For Islamic Studies, 2025)
This book review critically explores George Sale's pioneering translation of the Qur'an, focusing on its historical significance, linguistic nuances, and enduring relevance. Sale's translation, first published in 1734, remains a seminal work in English-language interpretations of the Qur'an. The review delves into Sale's dedication and introductory sections, highlighting his acknowledgment of the Qur'an's importance amidst differing religious perspectives. Drawing from Sale's own words and insights from orientalists like Edward Denison Ross, the review elucidates the Qur'an's role in shaping Islamic civilization and its impact on diverse cultures. Additionally, Sale's meticulous translation, influenced by earlier works such as Lewis Marracci's Latin translation, reflects the elegance and purity of the Arabic language, further underscored by its canonical status among Arabic-speaking communities. The review also examines Sale's comprehensive approach, encompassing not only translation but also contextual explanations and historical references. Furthermore, it discusses Sale's discourse on pre-Islamic Arabian society, the emergence of Islam, and the fundamental doctrines expounded in the Qur'an. The review concludes by advocating for the inclusion of Sale's preliminary discourse in future editions, emphasizing the enduring relevance of the Qur'an's truths for contemporary readers, both Muslim and non-Muslim alike.